Drain Versus No Drain After Total Knee Arthroplasty: A Retrospective Comparative Study at King Abdulaziz University Hospital - Emad A. Anam; Mohammed M. Abbas; Amro M. Al Hibshi (Journal of King Abdulaziz University: Medical Sciences, 2023)
To evaluate blood loss, infection rate, use of pain medication, and length of hospital stay in patients with and without drains post total knee arthroplasty. This was a retrospective comparative study on patients who had undergone total knee arthroplasty at King Abdulaziz University Hospital, Jeddah between 2006 and 2010. Patients were divided into two groups: drainage (n = 40) and no drainage (n = 40). The hemoglobin level, hematocrit level, use of pain medication, number of blood transfusions, and length of hospital stay were recorded. The patients were assessed for infection post surgery. Data were analyzed using SPSS program. There was a significant fall in the average levels of hemoglobin and hematocrit, and an increase in the blood transfusion rates in the drainage group than in the other group. There was one case of infection in the no drainage group. All patients’ were found using pain medications with no significant difference in the type of pain medication prescribed between the two groups. There was no significant difference in the average length of hospital stay between both groups. Drains increase the blood transfusion rate post total knee arthroplasty and have no effect on infection rate, pain control and length of hospital stay.